2015
DOI: 10.1016/j.autrev.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-binding, proinflammatory T cells identified by MCAM (CD146) expression: Characterization and role in human autoimmune diseases

Abstract: A subset of T cells defined by the cell surface expression of MCAM (CD146) has been identified in the peripheral circulation of healthy individuals. These cells comprise approximately 3% of the pool of circulating T cells, have an effector memory phenotype, and are capable of producing several cytokines. Notably, the MCAM positive cells are enhanced for IL-17 production compared to MCAM negative effector memory T cells. These call are committed for IL-17 production and do not require in vitro polarization with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 53 publications
0
49
0
Order By: Relevance
“…CD146 (also called melanoma cell adhesion molecule [MCAM]) is a cell adhesion glycoprotein expressed on lymphoid cells, endothelial cells, smooth muscle cells, and tumor cells, and displays homophilic or heterophilic interaction (50). It has been shown to play a major role in T cell migration through interaction with endothelial cells (33,43).…”
Section: Discussionmentioning
confidence: 99%
“…CD146 (also called melanoma cell adhesion molecule [MCAM]) is a cell adhesion glycoprotein expressed on lymphoid cells, endothelial cells, smooth muscle cells, and tumor cells, and displays homophilic or heterophilic interaction (50). It has been shown to play a major role in T cell migration through interaction with endothelial cells (33,43).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from LFA-1–ICAM-1-dependent penetration of the CP by T H 17 cells, we have recently shown that adhesion of T H 17 cells to an in vitro model of the BBB in the absence of VLA-4 involves melanoma cell adhesion molecule (MCAM; CD146) [ 17 ]. MCAM is an extracellular adhesion molecule broadly expressed on mesenchymally derived tissues [ 18 ]; in humans it has also been reported to be expressed on a subpopulation of IL-17-secreting CD4 + and CD8 + T cells (T H 17 and Tc17 cells, respectively) [ 18 25 ]. EAE experiments performed in endothelial MCAM knockout mice have shown reduced disease severity and reduced T H 17 infiltration into the CNS, supporting a role for this molecule in the entry of encephalitogenic T cells into the brain [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, anti-MCAM antibody therapy seemed to be potentially effective for the treatment of various Th17-mediated diseases 22 , suggesting that MCAM could play pathogenic roles in disease. Indeed, the MCAM level in endothelial cells is increased by TNF, and it acts to enhance both angiogenesis and migration of activated monocytes into in amed tissues, suggesting that MCAM may augment the pathogenesis of psoriasis 18 . As shown in Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 99%